Association between ankle torque and performance-based tests, self-reported pain, and physical function in patients with knee osteoarthritis - Cristiano Carvalho,; Glaucia Helena Gonçalves,; Luiz Fernando Approbato Selistre,; Marina Petrella,; Tatiana De Oliveira Sato,; Paula Regina Mendes Da Silva Serrão,; Stela Márcia Mattiello, (Archives of Rheumatology, 2023)
Objectives: This study aimed to investigate the association between ankle torque and performance-based tests, self-reported pain, and physical function in patients with knee osteoarthritis (OA). Patients and methods: The cross-sectional study was conducted with 39 individuals (24 females, 15 males; mean age: 57.3±6.2 years; range, 40 to 65 years) with knee OA between January 2014 and July 2015. Ankle torque was determined using an isokinetic dynamometer. The 40-m fast-paced walk test and a stair climb test were used to assess functional performance. Self-reported pain and physical function were assessed using the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC). Pearson’s correlation coefficients were calculated to test correlations between the dependent variables (40-m fast-paced walk test, stair climb test, WOMAC pain and physical function domains, sex, age, body mass index, and radiologic evidence of OA) and the independent variables (mean plantar flexor torque and dorsiflexor peak torque). A multiple linear regression analysis was applied to quantify the association between the dependent and independent variables. Results: Dorsiflexor and plantar flexor peak torques in the concentric and eccentric modes were negatively correlated with the 40-m fast-paced walk and stair climb tests (r=-0.33 to -0.51, p≤0.05). A negative correlation was found between concentric plantar flexor torque and the WOMAC physical function score (r=-0.35, p=0.03). No correlation was found between ankle torques and the WOMAC pain score (p>0.05). The multiple linear regression analysis showed that the eccentric plantar flexor and dorsiflexor torques were significantly associated with the stair climb test (β=-0.001, 95% confidence interval [CI]: -0.001 to 0.000, p=0.03, and β=-0.002, 95% CI: -0.004 to 0.000, p=0.05, respectively). No significant associations were found between concentric plantar flexor and dorsiflexor torques and the stair climb test (p>0.05). No significant associations were found between the ankle torques and the 40-m fast-paced walk test and WOMAC physical function (p>0.05). Conclusion: Ankle torque plays an important role in functional performance. Thus, ankle torque deficit, especially eccentric plantar flexor and dorsiflexor torques, may exert a negative influence on stair climbing performance in patients with knee osteoarthritis.